Round Robin Evaluation of MET Protein Expression in Lung Adenocarcinomas Improves Interobserver Concordance. Issue 9 (October 2020) - Boyle, Theresa A.; Khalil, Farah K.; Mino-Kenudson, Mari; Sica, Gabriel L.; Moreira, Andre L.; Sholl, Lynette M.; Knight, Mirna Z.; Zhang, Liping; Saller, James; Varella-Garcia, Marileila; Berry, Lynne D.; Chen, Heidi; et al.
Abstract : Introduction: Overexpression of the mesenchymal-epithelial transition (MET) receptor, a receptor tyrosine kinase, can propel the growth of cancer cells and portends poor prognoses for patients with lung cancer. Evaluation of MET by immunohistochemistry is challenging, with MET protein overexpression varying from 20% to 80% between lung cancer cohorts. Clinical trials using MET protein expression to select patients have also reported a wide range of positivity rates and outcomes. Materials and Methods: To overcome this variability, the Lung Cancer Mutation Consortium Pathologist Panel endeavored to standardize the evaluation of MET protein expression with "Round Robin" conferences. This panel used randomly selected Aperio-scanned formalin-fixed paraffin-embedded lung cancer specimens stained by MET immunohistochemistry for the Lung Cancer Mutation Consortium 2.0 study (N=838). Seven pathologists in separate laboratories scored images of 5 initial cases and 2 subsequent rounds of 39 cases. The pathologists' scores were compared for consistency using the intraclass correlation coefficient. Issues affecting reproducibility were discussed in Round Robin conferences between rounds, and steps were taken to improve scoring consistency, such as sharing reference materials and example images. Results: The overall group intraclass correlation coefficient comparing the consistency of scoring improved from 0.50 (95% confidence interval, 0.37-0.64) for the first scoring round to 0.74 (95% confidence interval, 0.64-0.83) for the second round. Discussion: We found that the consistency of MET immunohistochemistry scoring is improved by continuous training and communication between pathologists.